IMF Staff papers : Volume 16 No. 3. (IMF Staff Papers; IMF Staff Papers ;, 1969)
This paper presents a report on existing international banking and credit facilities in the Economic Commission for Asia and the Far East (ECAFE) region. The report presents a background formation on the importance of intraregional trade and payments, the exchange systems of the countries concerned, and banking relationships within the region. Balance of payments statistics of the ECAFE countries are not available in a form that would permit the calculation of intraregional payments for both trade and nontrade transactions. As far as nontrade transactions are concerned, there is reason to believe that the intraregional proportion is low. Although several countries of the ECAFE region have bilateral payments agreements with countries outside the region, especially with Eastern European countries, little of the trade among countries of the region is conducted under bilateral payments agreements. A mandatory system of clearing may be established by mutual agreement of the participating members. Alternatively, each member could retain the freedom to decide whether it would require all transactions to be settled through the clearing union or would leave it to traders to choose what they regard as the most advantageous method of settlement.